Volatile bodies: toward a corporeal feminism - Grosz, E. A. (Theories of representation and difference, 1994)
Volatile Bodies demonstrates that the sexually specific body is socially constructed: biology or nature is not opposed to or in conflict with culture. Human biology is inherently social and has no pure or natural "origin" outside of culture. Being the raw material of social and cultural organization, it is "incomplete" and thus subject to the endless rewriting and social inscription that constitute all sign systems. Examining the theories of Freud, Lacan, Merleau-Ponty, Foucault, Deleuze, Derrida, etc. on the subject of the body, Elizabeth Grosz concludes that the body they theorize is male. These thinkers are not providing an account of "human" corporeality but of male corporeality. Grosz then turns to corporeal experiences unique to women--menstruation, pregnancy, childbirth, lactation, menopause. Her examination of female experience lays the groundwork for developing theories of sexed corporeality rather than merely rectifying flawed models of male theorists.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; lit4700; premier cycle; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

L'illusion transsexuelle - Mercader, Patricia (Collection Psycho-logiques, 1994)
Naît-on transsexuel ou le devient-on? Quel est le sexe des transsexuels? Peut-on parler de droit à l'identité sexuelle?.... En confrontant les points de vue des acteurs sociaux engagés dans le "phénomène transsexuel" (médecins, psychanalistes, sociologues, juristes et bien sûr les transsexuels eux-mêmes), cela éclaire les enjeux de société que traduisent ces questions profondément éthiques.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexe/genre; shm4000; systèmes d'oppressions; thématiques; transféminisme